2006
DOI: 10.1002/bit.21049
|View full text |Cite
|
Sign up to set email alerts
|

Ultra scale-down studies of the effect of flow and impact conditions duringE. coli cell processing

Abstract: The ability to recover cells from a fermentation broth in an intact form can be an important criterion for determining the overall performance of a recovery and purification sequence. Disruption of the cells can lead to undesired contamination of an extracellular product with intracellular components and vice versa loss of intracellular products may occur. In particular, the value of directed location of a product in the periplasmic space of say Escherichia coli (E. coli) would be diminished by such premature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 51 publications
(77 reference statements)
1
28
0
Order By: Relevance
“…During fermentation, as the limit of the periplasm is reached, cells begin to lose viability and leak the Fab' product and other intracellular content to the fermentation broth. Apart from product loss in late stage fermentation, the remaining viable cells become more fragile and break fourfold more than those harvested at an earlier stage, if subjected to the equivalent shear level of that in an industrial centrifuge . As cell lysis occurs in late stage fermentation, leakage of product to the fermentation broth also acts to increase the broth viscosity, as large quantities of chromosomal DNA and other intracellular content are released simultaneously into the broth .…”
Section: Introductionmentioning
confidence: 99%
“…During fermentation, as the limit of the periplasm is reached, cells begin to lose viability and leak the Fab' product and other intracellular content to the fermentation broth. Apart from product loss in late stage fermentation, the remaining viable cells become more fragile and break fourfold more than those harvested at an earlier stage, if subjected to the equivalent shear level of that in an industrial centrifuge . As cell lysis occurs in late stage fermentation, leakage of product to the fermentation broth also acts to increase the broth viscosity, as large quantities of chromosomal DNA and other intracellular content are released simultaneously into the broth .…”
Section: Introductionmentioning
confidence: 99%
“…Similar effects might be reproduced during focused acoustics (Li et al, 2012; Wenger et al, 2008). During disruption by either mechanism there will broadly be two parallel processes occurring the first being the breakage of the cells to release intracellular components and cell ghosts (e.g., Chan et al, 2006) and the second being attrition or degradation of the released components including the cell ghosts and the poly nucleic acids. The extent of both processes is likely to be determined by the power dissipation and the mean residence time in the zone of highest power dissipation.…”
Section: Resultsmentioning
confidence: 99%
“…The main options for harvesting large volumes of culture are continuous centrifugation or microfiltration (Kong et al 2008). Previous studies have shown that E. coli cells harvested with an intermittent-discharge, continuous flow disc-stack centrifuge are subjected to stresses that are sufficiently high to cause lysis, especially if cells grown in a defined medium (Chan et al 2006). Typically, the centrifugation method used had a strong influence on sc pDNA yield and enhances in productivity could be obtained by an integrated approach between fermentation and centrifugation conditions.…”
Section: Primary Isolationmentioning
confidence: 99%